Estrategias de enfermería para prevenir embarazo en adolescentes atendidas en el Centro de Salud Punyaro - Velasco Portilla, Daniela Viviana (2024)
Teenage pregnancy has been a global concern due to its implications for the health and well-being for both the teenage mothers and their families; and this situation can also be considered as the product of a combination of social, economic, cultural and educational factors. This research aims to implement nursing strategies to prevent pregnancy in adolescents who attended the Punyaro Health Center located in the city of Otavalo. To this purpose, a qualitative- quantitative study was carried out, cross-sectional, based on applied, descriptive, bibliographic, field and narrative research, additionally supported by analytical-synthetic, historic-logic methods under a systemic approach. The research was applied to 80 adolescents, which allowed to identify the causes and factors that influence in the early pregnancy among teenagers. The model of health promotion proposed by Nola Pender was addressed to comprehend human behaviors related to health and similarly it was oriented to the generating of healthy behaviors, which emphasized the relevance of the process of standardized attention regarding the nursing care and the education towards them, which led to a proposal aimed to the nursing personnel and the teenager mothers. The application of Nursing Care Process played an essential role by the nursing staff and the education process for the adolescents, especially the population between 15 and 19 years old, given that this is the population’s range with most existing cases